Chinese Herbal Products for Non-Motor Symptoms of Parkinson’s Disease in Taiwan: A Population-Based Study - Lin, Chien-Hung; Chiu, Hsienhsueh Elley; Wu, Szu-Ying; Tseng, Shih-Ting; Wu, Tzu-Chan; Hung, Yu-Chiang; Hsu, Chung Y.; Chen, Hsuan-Ju; Hsu, Sheng-Feng; Kuo, Chun-En; Hu, Wen-Long (Frontiers in Pharmacology, 2021)
Objective: Combinations of Chinese herbal products (CHPs) are widely used for Parkinson's disease (PD) in Taiwan. Thereby, we investigated the use of CHPs for PD patients. Methods: This study was a population-based cohort study that analyzed the data of patients with PD from the National Health Insurance Research Database. A total of 9117 patients were selected from a random sample of 1 million individuals enrolled in this database. We used multiple logistic regression models to estimate the adjusted odds ratios of the demographic factors and analyzed the formula and single CHPs commonly used for PD. Results: Traditional Chinese medicine users were more commonly females, younger patients, those with white-collar status, and residents of Central Taiwan. Chaihu-Jia-Longgu-Muli-Tang was the most commonly used formula, followed by Ma-Zi-Ren-Wan, and Shao-Yao-Gan-Cao-Tang. The most commonly used single herb was Uncaria tomentosa (Willd. ex Schult.) DC., followed by Gastrodia elata Blume, and Radix et Rhizoma Rhei (Rheum palmatum L., Rheum tanguticum Maxim. ex Balf. and Rheum officinale Baill.) Chaihu-Jia-Longgu-Muli-Tang and Uncaria tomentosa (Willd. ex Schult.) DC. have shown neuroprotective effects in previous studies, and they were used for non-motor symptoms of PD. Conclusions: Chaihu-Jia-Longgu-Muli-Tang and Uncaria tomentosa (Willd. ex Schult.) DC. are the most commonly used CHPs for PD in Taiwan. Our results revealed the preferences in medication prescriptions for PD. Further studies are warranted to determine the effectiveness of these CHPs for ameliorating the various symptoms of PD and adverse effects of PD medications and the mechanisms underlying the associated neuroprotective effects.